Valproic Acid Protects Chondrocytes from LPS-Stimulated Damage via Regulating miR-302d-3p/ITGB4 Axis and Mediating the PI3K-AKT Signaling Pathway - Sun, Long; Zheng, Wei; Liu, Qian-Dong; Ge, Lei (Frontiers in Molecular Biosciences, 2021)
Background Osteoarthritis (OA) is one of most common degenerative joint disease characterized by increased apoptosis and autophagy deficiency. The investigation was performed to examine the effect of valproic acid (VPA) and molecular mechanism related to miR-302d-3p/ITGB4 axis in OA. Methods The OA clinical samples were obtained from GEO database to analyze differentially expressed genes. An in vitro OA model was mimicked by LPS in CHON-001 cells. Autophagy-related genes were downloaded from HADb website, and potential drugs were mined using CTD website. The upstream factors of ITGB4 were predicted with bioinformatics analysis, which was validated by luciferase activity assay and RIP assay. Cell viability and apoptosis were evaluated using CCK-8 and flow cytometry. The expression levels, including ITGB4, miR-302d-3p, and autophagy-/PI3K-AKT pathway-related markers, were measured by qRT-PCR or/and western blot. Results Our results showed that miR-302d-3p inhibited cell viability and promoted apoptosis of LPS-treated CHON-001 cells by targeting ITGB4. VPA treatment remarkably alleviated LPS-stimulated injury in CHON-001 cells. The inhibitory effect of VPA on LPS-stimulated damage in CHON-001 cells was weakened by miR-302d-3p overexpression, while intensified because of ITGB4 upregulation. Mechanistically, VPA treatment induced a significant decrease in the levels of p-PI3K and p-AKT in LPS-stimulated CHON-001 cells through regulating miR-302d-3p/ITGB4 axis. Conclusion Overall, VPA treatment may ameliorate LPS-induced injury on chondrocytes via the regulation of miR-302d-3p/ITGB4 pair and the inactivation of PI3K-AKT pathway.